Answer:
x=1
Step-by-step explanation:
Simplifying
6x + 5 = 11x
Reorder the terms:
5 + 6x = 11x
Solving
5 + 6x = 11x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-11x' to each side of the equation.
5 + 6x + -11x = 11x + -11x
Combine like terms: 6x + -11x = -5x
5 + -5x = 11x + -11x
Combine like terms: 11x + -11x = 0
5 + -5x = 0
Add '-5' to each side of the equation.
5 + -5 + -5x = 0 + -5
Combine like terms: 5 + -5 = 0
0 + -5x = 0 + -5
-5x = 0 + -5
Combine like terms: 0 + -5 = -5
-5x = -5
Divide each side by '-5'.
x = 1
Simplifying
x = 1